Nickel tetrasulphonated phthalocyanine (NITSPC) nanostructures via polycarbonate membrane: Enhancement on optical, morphological and electrical properties / Mirza Mohd Fawwaz Bin Faizan Beg - Faizan Beg, Mirza Mohd Fawwaz (2015)

(untitled)
Nickel tetrasulfonated phthalocyanine (NiTsPc) with planar aromatic structures is an ideal building block for organic nanostructures. NiTsPc can self-assemble into stacks through π–π interaction, exhibit high thermal and chemical stabilities, and possess outstanding electrical and optical properties. In this paper, the optical, morphological and electrical properties of NiTsPc nanostructures were investigated. NiTsPc nanostructures were synthesized via polycarbonate membrane of immersion technique. The polycarbonate membrane was immersed in NiTsPc solution for 1 hour and 24 hours. Different annealing temperatures of 50 °C and 100 °C were applied prior to the dissolution of polycarbonate membranes. NiTsPc nanostructures were characterised by UV-Vis spectroscopy, Raman spectroscopy, photoluminescence spectroscopy, field emission scanning electron microscopy and four point probes.